2020
DOI: 10.3390/tropicalmed5040173
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome Composition and Borrelia Detection in Ixodes scapularis Ticks at the Northwestern Edge of Their Range

Abstract: Lyme disease-causing Borrelia burgdorferi has been reported in 10–19% of Ixodes ticks from Alberta, Canada, where the tick vector Ixodes scapularis is at the northwestern edge of its range. However, the presence of Borrelia has not been verified independently, and the bacterial microbiome of these ticks has not been described. We performed 16S rRNA bacterial surveys on female I. scapularis from Alberta that were previously qPCR-tested in a Lyme disease surveillance program. Both 16S and qPCR methods were conco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
12
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 97 publications
(149 reference statements)
6
12
4
Order By: Relevance
“…Our results are not in complete coherence with other studies; [31][32][33][34] as those studies were conducted under a variety of different conditions to examine tick's microbiome. For example, Sperling et al, [34] analyzed the ticks collected off the cats and dogs from Alberta (Canada), whereas Kwan et al, [31] conducted their studies on Ixodes pacificus ticks. Several studies have also identified variation in microbiome among different tick species [35], sex [36][37], and geography [16,14].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results are not in complete coherence with other studies; [31][32][33][34] as those studies were conducted under a variety of different conditions to examine tick's microbiome. For example, Sperling et al, [34] analyzed the ticks collected off the cats and dogs from Alberta (Canada), whereas Kwan et al, [31] conducted their studies on Ixodes pacificus ticks. Several studies have also identified variation in microbiome among different tick species [35], sex [36][37], and geography [16,14].…”
Section: Discussioncontrasting
confidence: 99%
“…A variation in the microbiota of Ixodes ticks with regard to geography and sex has been suggested [14]. Our results are not in complete coherence with other studies; [31][32][33][34] as those studies were conducted under a variety of different conditions to examine tick's microbiome. For example, Sperling et al, [34] analyzed the ticks collected off the cats and dogs from Alberta (Canada), whereas Kwan et al, [31] conducted their studies on Ixodes pacificus ticks.…”
Section: Discussioncontrasting
confidence: 85%
“…Our results are not in complete coherence with other studies [30][31][32][33][34], as those studies were conducted under a variety of different conditions to examine the tick's microbiome. For example, Sperling et al [34] analyzed the ticks collected off the cats and dogs from Alberta (Canada), whereas Kwan et al [31] conducted their studies on Ixodes pacificus ticks. Several studies have also identified variation in microbiome among different tick species [35], sexes [36,37], and geographies [14,16].…”
Section: Discussioncontrasting
confidence: 99%
“…A variation in the microbiota of Ixodes ticks with regard to geography and sex has been suggested [14]. Our results are not in complete coherence with other studies [30][31][32][33][34], as those studies were conducted under a variety of different conditions to examine the tick's microbiome. For example, Sperling et al [34] analyzed the ticks collected off the cats and dogs from Alberta (Canada), whereas Kwan et al [31] conducted their studies on Ixodes pacificus ticks.…”
Section: Discussioncontrasting
confidence: 89%
“…The diagnostic value of 16S rRNA amplicon sequencing methods has not been thoroughly validated for tick-borne pathogens. One study, however, showed that ticks which tested positive for Borrelia using quantitative PCR methods also had a high abundance of Borrelia using amplicon bacterial metabarcoding [ 70 ]. Therefore, even though Ix.…”
Section: Discussionmentioning
confidence: 99%